2018
DOI: 10.1038/s41375-018-0114-0
|View full text |Cite
|
Sign up to set email alerts
|

Lenalidomide enhances MOR202-dependent macrophage-mediated effector functions via the vitamin D pathway

Abstract: Macrophages are key mediators of the therapeutic effects exerted by monoclonal antibodies, such as the anti-CD38 antibody MOR202, currently introduced in multiple myeloma (MM) therapy. Therefore, it is important to understand how antibody-mediated effector functions of myeloma-associated macrophages (MAMs) are regulated. Here, we focused on the effects of vitamin D, a known regulator of macrophage effector functions. Consequently, it was the aim of this study to assess whether modulation of the vitamin D pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 45 publications
0
27
0
Order By: Relevance
“…Patient-derived xenograft and in vitro phagocytosis studies showed that trabectedin enhanced antitumor functionality of monocytes and macrophages. These trabectedin-dependent effector cell mechanisms are reminiscent of the immunomodulatory activity of lenalidomide, a regulator of T-cell and macrophage function in CLL (33,46).…”
Section: Discussionmentioning
confidence: 99%
“…Patient-derived xenograft and in vitro phagocytosis studies showed that trabectedin enhanced antitumor functionality of monocytes and macrophages. These trabectedin-dependent effector cell mechanisms are reminiscent of the immunomodulatory activity of lenalidomide, a regulator of T-cell and macrophage function in CLL (33,46).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been demonstrated that, in particular, the CD16 + (FcγRIIIA) subset of monocytes is fundamental in DARA MM cells-killing activity [ 11 ]. In vitro studies have demonstrated that MOR202 can induce ADCP by myeloma-associated macrophages against MM cell lines [ 12 ]. On the other hand, ISA triggers ADCP only on MM cells that present a high level of CD38 molecules on the surface [ 13 ].…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…More recently, it has been suggested that vitamin D pathway activation can potentiate the synergism between LEN and MOR202-mediated ADCP [ 77 ] due to LEN ability to induce Cytochrome P450 Family 27 Subfamily B Member 1 (CYP27B1) expression in macrophages [ 12 ].…”
Section: Therapeutic Strategies Combining Anti-slamf7 or Anti-cd38mentioning
confidence: 99%
“…50% of myeloma cells from patients with normal karyotype del13q14-aberration and wildtype TP53. Conversely, TP53deficient patients displayed a significantly reduced treatment response of 6.4% phagocytosis even in high 10:1 effector-to target cell ratio ( Figure 2D) (Busch et al, 2018). Conversely, TP53-deficient patients displayed a significantly reduced treatment response of 6.4% phagocytosis, even in high 10:1 effector-to target cell ratio ( Figure 2D).…”
mentioning
confidence: 94%